2020
DOI: 10.1109/te.2019.2951568
|View full text |Cite
|
Sign up to set email alerts
|

JolasMATIKA: An Experience for Teaching and Learning Computing Topics From University to Primary Education

Abstract: A learning-by-teaching methodology through games can be used to promote informatics (computer science) in primary and secondary education. Applying the proposed activities can change students' perception of informatics from seeing it as merely using computers to seeing its relationship with mathematics. The experience can also help students acquire competences in teaching. Background: Although students, specifically in primary and secondary education, are increasingly competent in terms of technology use, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…To achieve this goal, we must adhere to the guiding ideology of all-round education in the whole process, give full play to the educational function of each role, and pay attention to every link and gateway of talent training [6]. Among them, "whole staff education" is the basis of "whole process education" and "all-round education".…”
Section: An Algorithm For Locating the Educationalmentioning
confidence: 99%
“…To achieve this goal, we must adhere to the guiding ideology of all-round education in the whole process, give full play to the educational function of each role, and pay attention to every link and gateway of talent training [6]. Among them, "whole staff education" is the basis of "whole process education" and "all-round education".…”
Section: An Algorithm For Locating the Educationalmentioning
confidence: 99%
“…The fun of the game, the stability of the technology, the simulation degree of simulation and other factors all have an impact on the degree of participation of the students. Enhancing student engagement can start from different solutions such as the game project itself, the problems in the simulation process, and the way of teaching behavior (Larraza-Mendiluze et al, 2020). Studies have shown that participants can improve selfefficacy and enhance trust in technology when interacting with AI technology (Brauner et al, 2019).…”
Section: Possible Uses Of Artificial Intelligence In Business Simulat...mentioning
confidence: 99%
“…Practice question sets for students to practice in their spare time, so that they can have a deeper understanding of what they have learned; 4) Reference answers for students to refer to after practicing, so that they can understand what they have done wrong and where they have gone wrong; 5) Online testing and automatic scoring system for examination papers, which has a randomized database of examination papers, and the topics of the papers are different for each time, but the examination papers are the same in terms of types of topics and difficulty, and the examination papers are also scored by automatic judging after finishing the examination papers, so that the students can understand what is still insufficient for them; 6) Animation demonstration, some of the more abstract issues, the form of animation to show the abstract problem specific, image, intuitive display to the students, so that the content of the teaching is more easily understood and accepted by students; 7) Computer communication and network teaching case library, including from the actual construction of the project extracted from the relevant computer communication and network engineering cases, the students through the study of engineering teaching cases, can more deeply appreciate the relevant computer communication and network engineering cases, the students will be able to learn more about the project teaching cases, the students will be able to learn more deeply about the project teaching cases. The students, through studying the engineering teaching cases, can more deeply appreciate the application of related computer communication and network technology in the actual engineering; 8) Course-related new technology lectures collection, we organize the course team teachers, some of the latest advances in computer communication and network technology, in the form of academic presentations, introduced to the students, so that the students are up-to-date with the latest technological advances related to the course, and keep up to date with the latest developments in the relevant technology [16][17][18].…”
Section: Building Teaching Resourcesmentioning
confidence: 99%